2016
DOI: 10.1007/s11207-016-1033-8
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energetic Particle Events with Protons Above 500 MeV Between 1995 and 2015 Measured with SOHO/EPHIN

Abstract: The Sun is an effective particle accelerator producing solar energetic particle (SEP) events during which particles up to several GeVs can be observed. Those events observed at Earth with the neutron monitor network are called ground level enhancements (GLEs). Although these events with a high energy component have been investigated for several decades, a clear relation between the spectral shape of the SEPs outside the Earth's magnetosphere and the increase in neutron monitor count rate has yet to be establis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Candidates for sub-GLEs should exceed SEPs energy of about 300 MeV/nucleon (Atwell et al, 2015;Kühl et al, 2017). There are several candidates for sub-GLE events, now included in the GLE database (gle.oulu.fi) .…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for sub-GLEs should exceed SEPs energy of about 300 MeV/nucleon (Atwell et al, 2015;Kühl et al, 2017). There are several candidates for sub-GLE events, now included in the GLE database (gle.oulu.fi) .…”
Section: Discussionmentioning
confidence: 99%
“…Note that the latter version has the best false alarm ratio, compared with the other proton‐based versions (see Table ). This improvement was obtained taking into account some findings in recent studies [ Sandberg et al , ; Kühl et al , ], which report that the pre‐event background measured by EPHIN is an order of magnitude lower than those given by GOES. That is, an extreme proton flux fluctuation in EPHIN data is probably more related to an actual proton enhancement; consequently, the probability of a randomly produced “1” associated with the EPHIN proton flux is lower.…”
Section: Evaluation Of the Umasep‐500 Using Soho/ephin Proton Datamentioning
confidence: 68%
“…Regarding the reason for the early proton flux enhancements measured by the EPHIN integral channel and the HEPAD‐P11 channel ( E > 700 MeV) shown in Figure and their similarity, we mention some recent studies that could probably explain them. Kühl et al [] carried a GEANT 4 simulation of the EPHIN instrument and found that there is a possible electron contamination of the EPHIN high energy proton measurements; the increased flux above 700 MeV is believed to be caused by electrons above 10 MeV associated to the same SEP event. Since relativistic >10 MeV electrons arrive first than protons, this contamination could explain the early EPHIN proton rises in both GLE events.…”
Section: Evaluation Of the Umasep‐500 Using Soho/ephin Proton Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, in Fig. 3 we present the scatter plots between the ~116 MeV SOHO/ERNE protons and protons detected by the GOES >100 MeV as reported by [Papaioannou et al 2016], left plot, and SOHO/EPHIN >500 MeV as given by [Kühl et al 2017], right plot. The log 10 -log 10 Pearson correlation coefficients and the bootstrapping uncertainty (based on 1000 calculations) are also given on each plot.…”
Section: B) Soho/erne Proton Event Catalogmentioning
confidence: 98%